Mosque Parking System: An Implementation Using Camera and IoT - Lalu Ahmad Naufal Gina Gahara; Kurniawan D. Irianto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
The rapid technological advancement has transformed various aspects of daily life, including parking management in mosque environments. Mosque parking administration often proves inefficient, particularly during religious holidays, leading to vehicle congestion, disorganized parking arrangements, and worshiper delays. This research develops an Internet of Things-based parking capacity calculation system using ESP32-CAM cameras that automatically detect vehicles. The system displays real-time information through a 20x4 I2C LCD and website interface, showing vehicle count, available slots, status (entry/exit), and timestamp data, with storage capabilities in Firebase. Designed using a Human-Centered Design approach, the system was implemented at Darussalam Ganjuran Mosque parking area and evaluated through black box testing. Results revealed 66.67% detection accuracy, successful real-time parking capacity information display, and effective vehicle history storage. Performance limitations included reduced accuracy in low lighting conditions, difficulty tracking high-speed vehicles, and camera resolution constraints. The system allows users to access current parking conditions while enabling mosque administrators to monitor parking areas efficiently.